2005
DOI: 10.32947/ajps.v2i1.424
|View full text |Cite
|
Sign up to set email alerts
|

Changes in serum levels of Total protein , Albumin and Globulin in patients with Behcet's Disease.

Abstract: In order to have an idea about some of biochemical changes which might play a role in the pathogenesis of Behcet's disease. Estimation of serum total protein, albumin, globulin and HLA typing were carried out in 70 patients with Behcets disease using colorematric, mathematic & microlymphocytotoxicity tests respectively, compared with 35 patients with recurrent oral ulcers, and 35 healthy control group.Hyperproteinemia, hyperglobulinemia with hypoalbuminemia were observed in those patients in comparison to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 5 publications
(9 reference statements)
0
3
0
Order By: Relevance
“…Our patient had elevated serum globulin and immunoglobulins including IgG and IgA. A Mediterranean study comparing 70 BD patients and 35 healthy controls demonstrated a significant elevation in the level of serum globulin (g/dl) in the BD group compared with healthy controls ( p < 0.001) ( 23 ). This hyperproteinemia was explained by an increase in the concentration of specific polyclonal immunoglobulins related to B-cell activation ( 23 ).…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Our patient had elevated serum globulin and immunoglobulins including IgG and IgA. A Mediterranean study comparing 70 BD patients and 35 healthy controls demonstrated a significant elevation in the level of serum globulin (g/dl) in the BD group compared with healthy controls ( p < 0.001) ( 23 ). This hyperproteinemia was explained by an increase in the concentration of specific polyclonal immunoglobulins related to B-cell activation ( 23 ).…”
Section: Discussionmentioning
confidence: 69%
“…The role of hyperglobulinemia and hyperimmunoglobulinemia in the pathogenesis of Behçet's disease (BD) is not clear but has been an area of some interest ( 23 , 24 ). Our patient had elevated serum globulin and immunoglobulins including IgG and IgA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation